Differentiated Instruction Based on Learning Styles in Chemistry Classrooms: A Systematic Review of Models, Outcomes, and Implementation Challenges - Hariyanto, Septian Ariq; Sulistyaningsih, Sulistyaningsih; Suprihatiningrum, Jamil (Universitas Pendidikan Mandalika, 2025)
This systematic literature review explores the integration of learning-style-based differentiated instruction with active learning models, particularly Problem-Based Learning (PBL) and Project-Based Learning (PjBL), in secondary chemistry education. The purpose of the review is to identify, synthesize, and critically analyze how a differentiated learning approach based on learning styles can be effectively activated with active learning models such as PBL and PjBL in the context of secondary chemistry education. Drawing on eleven peer-reviewed studies published between 2015 and 2025, the review identifies how differentiation strategies, when aligned with students' visual, auditory, and kinesthetic preferences, can enhance conceptual understanding, motivation, and critical thinking. The review reveals consistent positive outcomes across various learning domains, with differentiation applied through content, process, and product adjustments. However, it also uncovers persistent implementation challenges, including limited teacher training, resource constraints, and lack of institutional support. The situation analysis finds these findings within the frameworks of constructivist pedagogy and responsive teaching, emphasizing the importance of adaptable, student-centered instruction in chemistry education. The study concludes by recommending stronger systemic support, longitudinal research, and professional development to ensure the sustainable application of differentiated instruction in diverse chemistry classrooms.